The impact of online games on changing children's behavior at SMP Muhammadiyah - Asman, Asman; Muliani, Muliani; Amin, Amin (Journal of Indonesian Progressive Education, 2025)
This research aims impact of online gaming on changes in children's behavior, focusing on its negative impact on social and emotional development at SMP Muhammadiyah 1 Berbah. The method used was descriptive qualitative, this study involved six parents, six students, and one teacher, using observation, interviews, and documentation for data collection. The results showed that online gaming positively improved technological understanding, but negatively impacted social interaction, emotional stability, and eye health. Factors contributing to gaming addiction include lack of self-control and parental attention. This study underscores the important role of parents and teachers in managing students' use of technology to reduce adverse impacts, such as antisocial behavior and decreased academic performance. Additionally, the study highlights the need for balanced digital engagement strategies to help children develop healthier gaming habits. Future research could explore intervention programs that promote responsible gaming while enhancing students' social and emotional well-being.